2023
DOI: 10.3389/fonc.2023.1227864
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of germline BRCA1/BRCA2 variants in breast and ovarian cancer in Peru

Yomali Ferreyra,
Gina Rosas,
Alicia M. Cock-Rada
et al.

Abstract: BackgroundThere is an increasing amount of data from Latin America on the characterization of BRCA variants; however, there is limited information from Peru. We conducted a retrospective study to describe germline pathogenic/likely pathogenic(P/LP) variants and variants of uncertain/unknown significance (VUS) in the BRCA1 and BRCA2 genes in Peru, in patients with breast and ovarian cancer, candidates for treatment with poly (adenosine diphosphate–ribose) polymerase (PARP) inhibitors.MethodsThe patients were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…In this study, we observed that BRCA2 is the most frequently mutated gene, followed by BRCA1. These findings are consistent with global data indicating that PVs in BRCA genes account for a significant proportion of hereditary breast cancer cases [3,16,33,34] and that a higher proportion of PVs in BRCA2 are reported among these cases from Colombia [15], Puerto Rico [35], and Cuba [36], whereas BRCA1 PVs are more frequent in Mexico [37,38], Argentina [39], Brazil [40], and Peru [41]. Other HR-DDR genes, such as ATM, BARD1, CHEK2, PALB2, RAD51C, and RAD51D, were also identified in our cohort, albeit at a lower frequency.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we observed that BRCA2 is the most frequently mutated gene, followed by BRCA1. These findings are consistent with global data indicating that PVs in BRCA genes account for a significant proportion of hereditary breast cancer cases [3,16,33,34] and that a higher proportion of PVs in BRCA2 are reported among these cases from Colombia [15], Puerto Rico [35], and Cuba [36], whereas BRCA1 PVs are more frequent in Mexico [37,38], Argentina [39], Brazil [40], and Peru [41]. Other HR-DDR genes, such as ATM, BARD1, CHEK2, PALB2, RAD51C, and RAD51D, were also identified in our cohort, albeit at a lower frequency.…”
Section: Discussionsupporting
confidence: 91%